Análisis de Métricas de Paisaje en el Departamento del Amazonas entre Los Años 2002-2018 (2021)
The department of Amazonas as an important region in the Colombian territory due to the large percentage of water resources, natural parks, indigenous reserves and natural biodiversity has been the subject of different analyses due to deforestation, increased human interaction with nature and the effect of urban expansion. The landscape of the department of Amazonas is composed of a great diversity of land covers at level 3 based on Corine Land Cover classification as a basis for the analysis of landscape metrics between 2002 and 2018, using the Patch Analyst tool by means of spatial statistics methodologies, to determine variables by cover or landscape such as number of patches, areas of cover, relationships between area and perimeters among others to establish landscape composition analysis and changes of covers in the study area.